The Effect of Magnetic Field on Catalytic Properties in Core-Shell Type Particles - Westsson, Emma; Picken, Stephen; Koper, Ger (Frontiers in Chemistry, 2020)
Magnetic field effects can provide a handle on steering chemical reactions and manipulating yields. The presence of a magnetic field can influence the energy levels of the active species by interacting with their spin states. Here we demonstrate the effect of a magnetic field on the electrocatalytic processes taking place on platinum-based nanoparticles in Ar and O2-saturated electrolyte. We have identified a shift in the potentials representing hydrogen adsorption and desorption, present in all measurements recorded in the presence of a magnetic field. We argue that the changes in electrochemical behaviour are a result of the interactions between the magnetic field and the unpaired spin states of hydrogen.